2001
DOI: 10.1016/s0735-1097(01)01554-6
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of lipoprotein-associated phospholipase A2levels and the risk of future cardiovascular events in women

Abstract: In contrast to prior data among hyperlipidemic men, the current data suggest that Lp-PLA(2) is not a strong predictor of future cardiovascular risk among unselected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(113 citation statements)
references
References 21 publications
4
104
2
3
Order By: Relevance
“…This bears further elucidation. The lack of correlation between Lp-PLA 2 activity and hsCRP is consistent with other studies (11)(12)(13)(14), suggesting that the two risk markers may have an additive effect on predicting cardiovascular risk for individual patients.…”
Section: Lp-pla 2 Variabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…This bears further elucidation. The lack of correlation between Lp-PLA 2 activity and hsCRP is consistent with other studies (11)(12)(13)(14), suggesting that the two risk markers may have an additive effect on predicting cardiovascular risk for individual patients.…”
Section: Lp-pla 2 Variabilitysupporting
confidence: 90%
“…Recent epidemiology studies have examined the role of Lp-PLA 2 in predicting incident cardiovascular events (11)(12)(13)(14)(15). The majority of these studies have demonstrated that elevated Lp-PLA 2 (mass or activity) is an independent predictor of future events.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to hs‐CRP, Lp‐PLA2 has the advantage of being a more specific marker for cardiovascular risk 7. However, epidemiological studies conducted in different populations have found inconsistent results regarding whether Lp‐PLA2 can be used as a predictor of atherosclerosis 10. This controversy has fuelled the search for more effective prediction methods for cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Packard, Caslake and their colleagues have described a positive association between plasma Lp-PLA2 levels and incidence of coronary heart disease in case-controlled studies among males in Scotland Packard et al 2000). A similar association between plasma Lp-PLA2 mass and coronary heart disease has been observed in Caucasian females (Blake et al 2001).…”
Section: Discussionmentioning
confidence: 82%